THE ROLE OF LAVENDER IN MEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article describes the spread and medicinal properties of lavender plant, its medicinal properties with a wonderful smell, its use in the food industry, cosmetology and perfumery, and medicine.